ORGANIZATION OF TEACHER-STUDENT PEDAGOGICAL INTERACTION IN BLENDED LEARNING THROUGH MOBILE MESSENGERS - Varenina, Liudmila; Goncharov, Vitaly; Tonoyan; Bazhin, Grigoriy; Ismailova, Kholisakhon (Revista Inclusiones, 2020)
It is possible to ensure the high quality of educational services that would meet global standards only by informatizing education and implementing innovative information and communication technologies and creative organizational forms of learning into the educational process. The success of organizing blended learning at a higher education institution with the use of the most modern information and communication technologies is determined, first, by informatization as a primary trend in education and, second, by features of modern students as members of "Generation Z" or "digital generation" for whom the existence in a virtual digital environment is completely natural. The article deals with the organization of teacher-student pedagogical interaction through mobile messengers in the context of blended learning. Based on the results of an expert survey, the authors identify the benefits of organizing pedagogical interaction of the subjects of education through mobile devices, compare messengers and show the sequence of organizing pedagogical interaction between subjects of education through messengers.